PENINGKATAN HASIL BELAJAR IPAS SISWA SD MELALUI PENERAPAN MODEL PBL DENGAN PENDEKATAN DEEP LEARNING - Henryk P. Gonsales; Jibrael Leo Tallo; Elisabeth W. Lobo; Irene Yuningsih S. Luthfi; Merhin K. Taloen; Daniel W. Fointuna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model integrated with a deep learning approach in improving students’ learning outcomes in the IPAS subject at SDI Nunbaun Sabu, Kupang City, East Nusa Tenggara. The research employed a quantitative method using a one-group pretest–posttest design. The research sample consisted of 31 fifth-grade students at SDI Nunbaun Sabu, Kupang City, East Nusa Tenggara. Data were collected using a test instrument consisting of 20 items and were analyzed descriptively and inferentially through the Shapiro–Wilk normality test, Levene’s homogeneity test, and the Wilcoxon Signed Rank test. The results indicated a statistically significant improvement in students’ learning outcomes. Furthermore, the Wilcoxon test results were significant (p < 0.001) with an effect size of r = 0.87, indicating a large effect. The findings focus on students’ learning outcomes in two domains, namely the cognitive and affective domains. Therefore, the integration of PBL and deep learning is proven to be effective in enhancing students’ learning outcomes in IPAS, particularly on the topic of the water cycle at the elementary school level. Accordingly, this strategy is recommended for use in IPAS learning in elementary schools to optimally support students’ learning achievement.